Erebonyx catacumbae, n. gen. et sp.: a blind, troglobitic cricket from Brazil (Orthoptera, Grylloidea, Phalangopsidae) - de Mello, Francisco De A. G.; Ferreira, Rodrigo Lopes (Zootaxa, 2021)
Erebonyx catacumbae, new genus and species of a troglobitic phalangopsid cricket are described from Brazil. Few specimens were collected from a limestone cave located in the municipality of Campo Formoso, northern State of Bahia, in a semi-arid zone characterized by the Caatinga vegetation. A brief discussion on troglomorphisms is provided, as well as some ecological remarks and potential threats for this species.